SWASEMBADA KEDELAI: ANTARA HARAPAN DAN KENYATAAN (Forum Penelitian Agro Ekonomi, 2016)
This paper aims to describe the state of production and consumption of soybean, the use of technology by farmers, and the factors supporting self-sufficiency in soybean. The main problem of the soybean economy is the difficulty to boost production to meet the fast growing consumption.  Stagnation of soybean production is due to incompletely technology applications and the use of low quality seeds leaving a low level of productivity.  The current price of the locally produced soybean  is not able to compete with the imported soybean.  The factors supporting self-sufficiency are the invention of high yield seed variety and better cultivation technology which necessary to transfer to the farmers to achieve the same level of productivity as that in research level.  However, invention of high yield seed needs an improvement of seeds supply system, both in terms of production and distribution.  In this context, Indonesia has huge marginal land for extensification to increase soybean production, although technology engineering for this purpose is required.  The other important supporting factor is the import tariff application for soybean with bound rate of 27 percent, although this is not currently applicable. Indonesia has a potential crop to substitute soybean.  However, efforts to promote the consumption of this alternative crop substitution are required to gradually replace soybean in the Indonesian diet.
Keywords: soybean; self-sufficiency; technology; farming; land; kedelai; swasembada; teknologi; usahatani; lahan